2011
DOI: 10.1097/bot.0b013e318206f556
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Solution for Wound Coverage by Skin Stretching

Abstract: Viscoelastic properties of skin, ie, creep and stress relaxation, allow it to stretch beyond its normal state within a short period of time. Presented here is a technique of "wound coverage by skin stretching" that uses this principle. Kirschner wires were passed through the skin edges on either side of the wound margins. Dynamic traction was applied with traction bands improvised by the surgeon from surgical glove wrist rings. We used this method in eight patients to close 10 wounds that were not feasible to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 11 publications
0
13
0
2
Order By: Relevance
“…Based on the viscoelastic properties of normal skin, a skin-stretching device can use constant traction and maintain approximation to facilitate closing large wounds without applying tension. Many surgical designs 711 are available for treating large wound closures, but most special devices based on these designs require additional equipment and materials to achieve gradual wound closure. Using skin-traction beyond this level was reported by Escalera, 12 who attached rubber bands to staples applied to the skin edges.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the viscoelastic properties of normal skin, a skin-stretching device can use constant traction and maintain approximation to facilitate closing large wounds without applying tension. Many surgical designs 711 are available for treating large wound closures, but most special devices based on these designs require additional equipment and materials to achieve gradual wound closure. Using skin-traction beyond this level was reported by Escalera, 12 who attached rubber bands to staples applied to the skin edges.…”
Section: Discussionmentioning
confidence: 99%
“…Wound dehiscence, wound edge necrosis, and skin tears are the most reported complications [ 14 , 30 , 31 ] (Table 2 ). Studies showed that the wound approximation technique was associated with relatively high wound dehiscence (20–33%) [ 8 , 30 , 31 ]. However, no patient developed wound dehiscence in this small series.…”
Section: Discussionmentioning
confidence: 99%
“…The biggest problem of this technique was the need of daily returns to the operating room, which made treatment difficult. Since then, the elastic band has been used in intervention of various types of wounds, including compartmental syndrome 10,11 , extensive fasciotomy wounds [12][13][14][15] , open fractures 16 , injuries from burns 17 and large wounds of the body wall 15,18 .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…The use of elastic bands to traction the wound edges is an effective resource in the treatment of large wounds of the body wall [9][10][11][12][13][14][15][16][17][18] . This closure occurs by skin stretching, using the viscoelastic properties of the skin 12,13,16,18 .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%